The Effect of Emotional Intelligence and Job Stress on Nurse Commitment with Satisfaction as a Mediation Variable - Herrik Yuza; Hendra Lukito (Management Institute Faculty of Economics Universitas Andalas, 2022)
This study aims to examine and analyze the effect of emotional intelligence and work stress on nurse commitment with satisfaction as a mediating variable at Andalas University Hospital, Padang. The population is all employees at Andalas University Hospital. The sampling method used is the census method. The research data was collected by distributing questionnaires to 75 respondents. Data processing and analysis was carried out using SmartPLS. The results showed that emotional intelligence, job stress and job satisfaction had a significant effect on nurse commitment, emotional intelligence and work stress had a significant effect on job satisfaction and job satisfaction served as a partial mediation between emotional intelligence and work stress on nurse commitment.